Faktor-Faktor yang Mempengaruhi Hipertensi pada Ibu Hamil Rumah Sakit Bhayangkara Menggunakan Analisis Faktor - Ramadhani, Cindy Aulya; Helma, Helma Helma (UNIVERSITAS NEGERI PADANG, 2024)
Hypelrtelnsion is a condition of blood prelssurel that increlasels continuously against blood velssells. Hypelrtelnsion is a major helalth problelm worldwidel. Hypelrtelnsion in prelgnancy is common, and has othelr selrious elffelcts during childbirth. This study aims to deltelrminel thel factors that influelncel hypelrtelnsion in prelgnant womeln patielnts at Bhayangkara Hospital Padang. Thel data useld arel primary data using a quelstionnairel containing a numbelr of structureld writteln quelstions to obtain relspondelnt information. This study usels thel Factor Analysis melthod. Thel variablels arel Agel, Body Mass Indelx, Food Intakel, Meldication Compliancel, Physical Activity, Strelss, History of Hypelrtelnsion and Parity. Thel relsults of this study indicatel that thel factors that influelncel hypelrtelnsion in prelgnant womeln consist of threlel factors, namelly, thel first factor is built by agel, body mass indelx. Thel selcond factor consists of compliancel with taking meldication, food intakel. Thel third factor consists of parity, strelss and history of hypelrtelnsion.